From Virtue to Vice Negotiating Anorexia - O'Connor, Richard A. (Food, Nutrition, and Culture, 2015)
The recovered possess the key to overcoming anorexia. Although individual sufferers do not know how the affliction takes hold, piecing their stories together reveals two accidental afflictions. One is that activity disorders-dieting, exercising, healthy eating-start as virtuous practices, but become addictive obsessions. The other affliction is a developmental disorder, which also starts with the virtuous-those eager for challenge and change. But these overachievers who seek self-improvement get a distorted life instead. Knowing anorexia from inside, the recovered offer two watchwords on helping those who suffer. One is "negotiate," to encourage compromise, which can aid recovery where coercion fails. The other is "balance," for the ill to pursue mind-with-body activities to defuse mind-over-body battles